Language Acquisition and Development : Proceedings of GALA 2007. - Gavarro, Anna; Freitas, M. Joao (Cambridge Scholars Pub., 2008)
This volume gathers fifty papers from the conference Generative Approaches to Language Acquisition, GALA 2007, celebrated in Barcelona between the 6th and 8th of September, 2007. It covers the areas of syntax and phonology of child language from the theoretical perspective of generative grammar - the theoretical outlook which first placed language acquisition at the centre of linguistic inquiry.